Isometric immersions into Riemannian Manifolds (2011)
This paper summarizes the basic theory of connections in principal bundles and vector bundles in order to apply these theories to the study of isometric immersions in Riemannian manifolds; by an appropriate version ofthe Frobenius theorem we show a result that generalizes the Fundamental Theorem of isometric immersions.